Manfaat Active Exercise terhadap Fungsi Berjalan Anak Usia 3–5 Tahun Pasca Operasi DDH: Studi Kasus - Yuan Fyrraliany; Ezra Bernadus Wijaya; Slamet Sumarno (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Developmental Dysplasia of the Hip (DDH) in children often results in joint stiffness, muscle weakness, limited range of motion, and gait impairment following surgical management and immobilization. Early physiotherapy intervention is essential to restore hip function and walking ability. This study aimed to evaluate the effectiveness of active exercise on functional walking in outpatient children aged 3–5 years after DDH surgery. A case study design was conducted on three female patients who completed a five-week rehabilitation program consisting of ten active exercise sessions, including hip strengthening, mobility training, and balance exercises, combined with a home program. Outcome measures included hip range of motion, Manual Muscle Testing, and Modified McKay and Harris Hip Score assessed at baseline, mid-intervention, and post-intervention. The results showed improvements in hip range of motion, particularly in flexion, extension, abduction, adduction, and external rotation, while internal rotation improved but did not reach normal values. Muscle strength increased from grade 1–2 to grade 3 in most hip muscle groups. Functional walking scores improved from poor to good and excellent, with patients achieving independent, symmetrical gait without pain. These findings indicate that active exercise is an effective rehabilitation approach to reduce impairments and enhance functional walking in children after DDH surgery. The study highlights the importance of structured physiotherapy and caregiver involvement to optimize recovery and participation in daily activities.